Research Designs and Methods in Self-assessment Studies: A Content Analysis - Serafina Pastore (International Journal of Evaluation and Research in Education (IJERE), 2017)
This paper focuses on self-assessment practices in the higher education field. In the assessment for learning perspective, self-assessment is related to reflection, metacognition, and self-regulation: all these aspects are considered as fundamental prerequisites for students’ future professional development. Despite the recognition of self-assessment educational benefits and implications, research so far lags behind the rise in the rates of align literature review, research design, and methodology. The study attempts to address this gap in the literature. Based on a critical review of institutional changes in the European higher education context, the paper reflected on main issues and problems faced by educational research on self-assessment. It then tried to identify future research pathways on this topic.